Electrospun VSe1.5/CNF composite with excellent performance for alkali metal ion batteries. Issue 35 (19th July 2019) - Xu, Lihong; Xiong, Peixun; Zeng, Lingxing; Fang, Yixing; Liu, Renpin; Liu, Junbin; Luo, Fenqiang; Chen, Qinghua; Wei, Mingdeng; Qian, Qingrong
Abstract : The VSe1.5 /CNF composite was fabricated as a superior performance anode material for alkali metal ion batteries. Abstract : Exploring advanced anode materials with excellent electrochemical performance for rechargeable batteries, including lithium-ion batteries (LIBs), sodium-ion batteries (SIBs) and potassium-ion batteries (PIBs), has attracted great attention. However, low electronic conductivity, severe particle agglomeration and lack of effective synthesis methods have still greatly hampered their rapid development. Herein, we initially fabricate a novel VSe1.5 /CNF composite through a facile electrospinning method followed by selenization. The electrochemical measurements show that VSe1.5 /CNFs can enable the rapid and durable storage of Li +, Na +, and K + ions. When used as an anode material for LIBs, the VSe1.5 /CNF composite delivers a high capacity of 932 mA h g −1 after 400 cycles at a high current density of 1 A g −1 . In addition, for SIBs, the VSe1.5 /CNF composite manifests a high reversible capacity of 668 mA h g −1 after 50 cycles and an excellent capacity of 265 mA h g −1 at 2 A g −1 even after an ultra-long 6000 cycles. This is one of the best performances of vanadium-based anode materials for SIBs reported so far. Most remarkably, the VSe1.5 /CNF composite also demonstrates a satisfactory reversible K + storage performance. The simple synthetic route and excellent ion storage properties make the VSe1.5 /CNF composite a great prospect for application as an anode material for alkali metal ion batteries.